Targeted individual prophylaxis offers superior risk stratification for cytomegalovirus reactivation after liver transplantation. Issue 12 (5th November 2015) - Sood, Siddharth; Haifer, Craig; Yu, Lijia; Pavlovic, Julie; Gow, Paul J.; Jones, Robert M.; Visvanathan, Kumar; Angus, Peter W.; Testro, Adam G.
Abstract : Cytomegalovirus (CMV) can reactivate following liver transplantation. Management of patients currently considered low risk based on pretransplant serology remains contentious, with universal prophylaxis and preemptive strategies suffering from significant deficiencies. We hypothesized that a CMV‐specific T cell assay performed early after transplant as part of a preemptive strategy could better stratify "low‐risk" (recipient seropositive) patients. We conducted a prospective, blinded, observational study in 75 adult recipients. QuantiFERON‐cytomegalovirus was performed both before and at multiple times after transplant. Low‐risk patients (n = 58) were monitored as per unit protocol and treatment was commenced if CMV > 1000 copies/mL (DNAemia). Twenty patients needed antiviral treatment for other reasons and were censored (mainly for rejection or herpes simplex virus infection); 19/38 (50%) of the remaining low‐risk patients developed DNAemia at mean 34.6 days after transplant. A week 2 result of <0.1 IU/mL was significantly associated with risk of subsequent DNAemia (hazard ratio [HR], 6.9; P = 0.002). The positive predictive value of 80% suggests these patients are inappropriately labeled low risk and are actually at high likelihood of CMV reactivation. A secondary cutoff of <0.2 IU/mL was associated with moderate risk (HR, 2.8; P = 0.01). In conclusion, a protocol based on a single early CMV‐specific T cell based assay would offer improved risk stratification and individualization of patient management after transplant. This could offer improved drug and service utilization and potentially result in significant improvements over both currently used protocols to manage supposedly low‐risk patients. Liver Transpl 21:1478‐1485, 2015 . © 2015 AASLD.